2014
DOI: 10.4028/www.scientific.net/amm.711.214
|View full text |Cite
|
Sign up to set email alerts
|

The New Progressive Polymeric Materials for the Reduction of VOC in the Woodworking Industry

Abstract: The paper deals with the preparation of new type of progressive polymer blends created from bicomponent synthetic fibres (PP/PA6) with addition of interfacial agent maleine-anhydrid (MAH) and polymeric mixtures with varying content of the polyamide component for the purpose of subsequent production of a highly efficient filters for collection of hazardous chemical (VOC) in processes surface finishing and treatment of wood products. Morphological parameters were studied in relation to the supramolecular structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Sulphur in the burning process is converted to sulfur oxides which are pollutant to the environment and also be irritating to the human respiratory system. ( [23,24,25]). The Sulphur content ranges from 0.00% for Burkea africana (Asapa), Funtumia elastica (Ire) and Milletia thonningii (Ito) to 1.03% for Hevea brasilensis (Rubber).…”
Section: Resultsmentioning
confidence: 99%
“…Sulphur in the burning process is converted to sulfur oxides which are pollutant to the environment and also be irritating to the human respiratory system. ( [23,24,25]). The Sulphur content ranges from 0.00% for Burkea africana (Asapa), Funtumia elastica (Ire) and Milletia thonningii (Ito) to 1.03% for Hevea brasilensis (Rubber).…”
Section: Resultsmentioning
confidence: 99%
“…The results of quantitative content present dangerous chemicals (selected from the VOC) produced during thermal loading of surface treated wood coating system Chemolak are shown in Table 3. It was found that the thermal degradation of cross-linked thermosetting polyurethane coatings PUR decomposition to toxic isocyanates, which are further degraded to benzene and carbon monooxide (CO -combustible toxic gass) [3]. PUR binder of emitted solvents: toluene, xylene and formaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…Solvent-based coatings are sources of volatile organic compounds (VOC) emissions that cause serious health problems (carcinogenic, harmful, irritant effects) [2]. The production of these dangerous chemicals takes place in the processes applied to the wood surface [3]. To release emissions may occur when burning wood with applied solvent based polyurethanes, which are frequently used in the finalization of wood products.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations